Analisis Pengaruh Rasio Keuangan Terhadap Financial Distress Pada PT Sri Tugu Muda Lampung - Hairudin Hairudin; Umar Bakti; Heylin Idelia Jayasinga (Universitas Mitra Indonesia, 2021)
The purpose of this research is to know the influence of liquidity ratio variable, leverage ratio, profitability ratio, and activity ratio to financial distress in PT. Sri Tugu Muda (Lampung). The tool analysis that used in this assumption that consist of some tests of normality,multikolineriety,heteroskedasticity and autocorrelation. The statistic anaysts that used are multiple linier regression and hipotesyst test which consist of t and F test also determination coeficient (R2 ). The dependent variable in this research is financial distress. While the independent variables are liquidity ratio, leverage ratio, profitability ratio and activity ratio. The result of the research shows partially of liquidity ratio that significanly influenced to financial distress. While leverage and profitability ratio is not significanly influenced to financial distress. Simultaneously, liquidity, leverage, profitability and activity ratio together influential significanly forward financial distress. This is evidenced R Square value of 0.697 the point is 69,7% of financial distress is influenced by the ratio of liquidity, leverage ratio, profitability, and activity ratio. And for 30,3% is influenced by another variables not reviewed in this reseach.